THE EFFECT OF MARKET ORIENTATION AND DISTRIBUTION CHANNELS ON MARKETING PERFORMANCE (Study on SMEs in the metal industry in Ngingas Waru Village) - Ahnaf Manaf; Widyastuti (International Journal of Social, Economic, and Business, 2024)
MSMEs play a vital role in Indonesia's economy, contributing approximately 61% to the national GDP. The processing industry sector leads with an average turnover of 28.25% or 450 billion Rupiah. Ngingas Village, a hub for metal industry MSMEs since 1930, is known as the "metal village," with MSMEs growing from fewer than 100 to around 320 by 2023. Despite this growth, sales turnover remains stagnant due to internal challenges like HR management and marketing, as well as external factors such as government policies and the global economy. Interviews in March 2024 revealed that market-oriented MSMEs in Ngingas Village, despite collaborations, still face sales fluctuations. This study examines the influence of market orientation and distribution channels on marketing performance using a quantitative approach. Data collected from 70 respondents via purposive sampling was analyzed with multiple linear regression in SPSS 25. Results indicate that market orientation positively and significantly impacts marketing performance, while distribution channels have no significant effect.